Catheter ablation for atrial fibrillation in the elderly >75 years old: Systematic review and meta‐analysis. (30th May 2022) - Prasitlumkum, Narut; Tokavanich, Nithi; Trongtorsak, Angkawipa; Cheungpasitporn, Wisit; Kewcharoen, Jakrin; Chokesuwattanaskul, Ronpichai; Akoum, Nazem; Jared Bunch, Thomas; Navaravong, Leenhapong
Abstract: Introduction: Atrial fibrillation (AF) ablation is increasingly performed worldwide. As comfort with AF ablation increases, the procedure is increasingly used in patients that are older and in those with more comorbidities. However, it is not well established whether AF ablation in the elderly, especially those >75 years old, has comparable safety and efficacy to younger populations. Objective: To compare the efficacy and safety profiles in patients older than 75 years undergoing AF ablation with younger patients. Methods: Databases from EMBASE, Medline, PubMed, and Cochrane, were searched from inception through September 2021. Studies that compared the success rates in AF catheter ablation and all complications rates between patients who were older vs under 75 years were included. Effect estimates from the individual studies were extracted and combined using random effect, generic inverse variance method of DerSimonian and Laird. Results: Twenty‐seven observational studies were included in the analysis consisting of 363, 542 patients who underwent AF ablation. Comparing patients older than 75 years old to younger patients, there was no difference in the success of ablation rates between elderly and younger patients (pooled OR 0.85: 95% CI:0.69–1.05, p = .131). On the other hand, AF ablation in the elderly was associated with higher complication rates (pooled OR 1.42: 95% CI:1.21–1.68, p < .001). Conclusion: As AF ablation is expanded to elderly populations, our study found that AF ablation success rates were similar in both elderly and younger patients. However, older patients experience higher rates of complications that should be considered when offering the procedure and as a means to improve outcomes with future innovations.